2021
DOI: 10.1016/j.icarus.2020.114004
|View full text |Cite
|
Sign up to set email alerts
|

Airfall on Comet 67P/Churyumov–Gerasimenko

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 94 publications
1
38
0
Order By: Relevance
“…Migliorini, A. et al 2016;Gasc et al 2017) discovered spatial and temporal variations in the coma H 2 O/CO 2 ratios, implying non-uniform mixing ratios for these two volatiles within the nucleus. As shown by Davidsson et al (2021Davidsson et al ( , 2022 for 67P, this could be caused by physical/chemical evolution of the comet's surface layers due to anisotropic illumination of the comet, but primordial variations in the H 2 O/CO 2 ratio intrinsic to the nucleus are also possible. It is therefore plausible that CH 3 OH in C/2016 R2 exists as a component within an apolar ice matrix dominated by CO and CO 2 , and some of this CH 3 OH is released into the coma when CO sublimates (as observed).…”
Section: Comparison With Previous Observations Of This Cometmentioning
confidence: 99%
“…Migliorini, A. et al 2016;Gasc et al 2017) discovered spatial and temporal variations in the coma H 2 O/CO 2 ratios, implying non-uniform mixing ratios for these two volatiles within the nucleus. As shown by Davidsson et al (2021Davidsson et al ( , 2022 for 67P, this could be caused by physical/chemical evolution of the comet's surface layers due to anisotropic illumination of the comet, but primordial variations in the H 2 O/CO 2 ratio intrinsic to the nucleus are also possible. It is therefore plausible that CH 3 OH in C/2016 R2 exists as a component within an apolar ice matrix dominated by CO and CO 2 , and some of this CH 3 OH is released into the coma when CO sublimates (as observed).…”
Section: Comparison With Previous Observations Of This Cometmentioning
confidence: 99%
“…As explained in Section 4.1, grain fragmentation can cause a steepening or a shallowing of the radial profile slope depending on the composition of the grain. Depending on the icy-grain environments, such as quick fragmentation of icy grains, sublimation of icy grain, or even icy-grain mantling, for example, could result in different radial profiles provided that the icy grains survive long enough (e.g., Beer et al 2006;Markkanen & Agarwal 2020;Davidsson et al 2021). This, combined with the radar measurements, suggests that if icy grains were present in either 45P/HMP, 46P/Wirtanen, or both, an icy dust halo could be present, creating a shallowing of the radial profile slope.…”
Section: Dust Grain Behavior's Effects On Radial Profilesmentioning
confidence: 99%
“…However, this model may be oversimplified and physical parameters related to the particle bed and boulder could not be derived. Additionally, Davidsson et al (2020) suggested a net accumulation of air fall material in this region of up to 3.6 m based on a numerical model including orbit dynamics, thermophysics of the nucleus, and hydrodynamics of the gas flow. In the following, we complement our measurements A2, page 3 of 15 A&A 662, A2 (2022)…”
Section: Bedform Description and Distributionmentioning
confidence: 99%